Complex function theory - Fujiwara, Takeo (Singapore : World Scientific, 2024)
The basics of complex functions will be explained for students of Engineering Sciences, with the aim of being able to use (3z(Bcomplex function theory(3y (Bas a tool. The goal is not rigor as mathematics, but ease of use that may suit the application. Explanations are based on concrete examples rather than abstract general theory. The book starts from very beginning of complex numbers, and extends theory of Introduction to Elliptic Function and Hypergeometric Differential Equations.s
Includes bibliography and index
Keywords: Functions of complex variables; Complex analysis; Conformal transformation; Elementary functions